Perencanaan Model Arsitektur Bisnis, Arsitektur Sistem Informasi dan Arsitektur Teknologi Dengan Menggunakan TOGAF: Studi Kasus Bakosurtanal - Iyan Supriyana (Generic, 2010)
The Information Technology was rapidly developed and it has affected on developing business. Information Technology is a necessary in BAKOSURTANAL to support some business in relation with data and spatial information. Users will get the advantage of easy and fast access to data and spatial information. The enterprise architecture takes role to support company, by facilitating the technology and process structure such as fundamental in information technology strategy. Enterprise architecture planning should be managed based on standardize framework in accordance to the world wide basic architecture framework reference. Architecture framework will accelerate and simplify the development of enterprise architecture, ascertaining comprehensive coverage of solutions, ensure that the result of enterprise architecture is in line with the growth of BAKOSURTANAL. This paper will study through the standard configuration of enterprise architecture. There are several framework of enterprise architecture e.g.: Zachman Framework, TOGAF (The Open Group Architecture Framework), etc. The result of this research showed that the most suitable enterprise architecture framework for BAKOSURTANAL’s blueprint development and to propose enterprise architecture model (business architecture, information system architecture, technology architecture) and to give suggestion or recommendation on technical basics shall be implemented as the architecture has been chosen.